Exploring Local Wisdom in Buginese Ethnics: Language Politeness Phenomena of Tau Soppeng - Alam, Fiptar Abdi; Al-Muthmainnah, Al-Muthmainnah (REiLA : Journal of Research and Innovation in Language, 2020)
The objectives of this research are to explore and to reveals the form and the characteristics of linguistic politeness, politeness strategies, and the realization of local wisdom found among Soppeng people (to Soppeng) one particular Buginese ethnics. This research applied ethnolinguistics viewed from pragmatics, semiotics, and politeness theories. To capture the data, this study used purposive sampling and snowball among native in Soppeng regency which agrees to be a part of this study. The method used is the method of listening with free engaged, recording, documentation, elicitation technique, and interview. The results of this research show the characteristics and the forms of linguistic politeness through some morphemes marked (such as prefixes ta), suffix pronouns (ta, ki, ni), some honorific vocabularies (such as pung, andi, daeng), some lexemes (iye, tabe, taddampengenga), some maxims of politeness principles; generosity, approbation, modesty, and sympathy, and four strategies of linguistic politeness i.e., bald on record, positive, negative, off-record strategy. In addition, this study also found the realization and the implication of local wisdom as a primary value such as ethics and language politeness, self-image, courage, solidarity, and cooperation.